Погляд в минуле, або як Г. М. Добров упроваджував результати наукових досліджень - Ісакова, Н.Б. (Наука та наукознавство, 2018)
Статтю присвячено проблемі ефективності наукових досліджень і впливу управлінської компетентності вчених на керівництво науковими колективами на рівні організацій і окремих підрозділів. Статья посвящена проблеме эффективности научных исследований и влияния управленческой компетентности ученых на руководство научными коллективами на уровне организаций и отдельных подразделений. The article’s objective is to make a retrospective analysis of the organization of the system for training of management staff in the Academy of Sciences of in the Academy of Sciences of the Ukrainian Soviet Socialist Republic (AS of UkrSSR) in the 1980s, to enhance the performance of research work. A review of science policy studies is given, with highlighting the contribution of G.M. Dobrov and his Kyiv scientific school.